The effect of socioeconomic status on three-year mortality after first-ever ischemic stroke in Nanjing, China - Zhang Renliang; Liu Xifei; Xu Gelin; Liu Xinfeng; Zhou Guangyi; Zhu Wusheng (BMC, 2006)
Abstract Background Low socioeconomic status (SES) is associated with increased mortality after stroke in developed countries. This study was performed to determine whether a similar association also exists in China. Methods A total of 806 patients with first-ever ischemic stroke were enrolled in our study. From August 1999 to August 2005, the three-year all-cause mortality following the stroke was determined. Level of education, occupation, taxable income and housing space were used as indicators for SES. Stepwise univariate and multivariate COX proportional hazards models were used to study the association between the SES measures and the three-year mortality. Results Our analyses confirmed that occupation, taxable income and housing space were significantly associated with three-year mortality after first-ever stroke. Manual workers had a significant hazard ratio of 5.44 (95% CI 2.75 to 10.77) for death within three years when compared with non-manual workers. Those in the zero income group had a significant hazard ratio of 5.35 (95% CI 2.95 to 9.70) and those in the intermediate income group 2.10 (95% CI 1.24 to 3.58) when compared with those in the highest income group. Those in two of the three groups with the smallest housing space also had significant hazard ratios of 2.06 (95% CI 1.16 to 3.65) and 1.68 (95% CI 1.12 to 2.52) when compared with those in group with the largest housing space. These hazard ratios remained largely unchanged after multivariate adjustment for age, gender, baseline cardiovascular disease risk factors, and stroke severity. The analyses did not confirm an association with educational level. Conclusion Lower SES has a negative impact on the outcome of first-ever stroke in Nanjing, China. This confirms the need to improve preventive and secondary care for stroke among low SES groups.